Wasiat Penggunaan Organ Tubuh Mayat; Studi Komparasi Pandangan Nahdlatul Ulama dan Muhammadiyah - Mita Ayu Lestari; Supardin Supardin (Universitas Islam Negeri Alauddin Makassar, 2021)
Articles have discussed about the will of the use of organs of the body of the bodies based on the angle of view of Nahdlatul Ulama and Muhammadiyah . The type of research that used the author of the study this is the kind of research qualitative , that which is the kind of research that brings a source of data research library of the form books or other scientific works . using the approach of normative ( Shari'a ), which is an approach to the problem that will be investigated based on the texts of the Koran, the Sunnah , and the consensus of the scholars and obtained from a variety of literature that is associated with the problems that will authors discuss both the sourced from primary data and secondary data . The results of the research have demonstrated their differences in opinion between the Nahdlatul Ulama and Muhammadiyah associated testament use of organs of the body of a corpse with methods istinbat law respectively . Based on the view of the Nahdlatul Ulama practice will use the organs of the body cadaver ruling is not valid ( void ) because did not meet any of the requirements will the absolute al- Milki who studied with methods ilhaqi . While on the terms of the views of Muhammadiyah practice will use the organs of the body corpse memperbolekan and assume legal permissible , where Muhammadiyah using methods istislahi namely to consider kemaslahatannya .Keywords : Testament ; Nahdlatul Ulama ; Muhammadiyah